Gravity and Migration before Railways: Evidence from Parisian Prostitutes and Revolutionaries - Morgan Kelly; Cormac Ó Gráda (European Historical Economics Society (EHES), 2018)
Although urban growth historically depended on large inflows of migrants, little is known of the process of migration in the era before railways. Here we use detailed data for Paris on women arrested for prostitution in the 1760s, or registered as prostitutes in the 1830s and 1850s; and of men holding identity cards in the 1790s, to examine patterns of female and male migration. We supplement these with data on all women and men buried in 1833. Migration was highest from areas of high living standards, measured by literacy rates. Distance was a strong deterrent to female migration (reflecting limited employment opportunities) that falls with railways, whereas its considerably lower impact on men barely changes through the nineteenth century.
Keywords: N33; N93; O15; R23; 330; Migration; gravity; prostitution